Change of tourism organizations: Implications from a review of cultural tourism research - Zhang, Ziling; Guo, Muyang (Frontiers in Psychology, 2022)
Change has been universally acknowledged as the perpetual theme for routine organizational life. As cultural tourism, a major element of global tourism consumption accounting for 40% of tourism employment, is becoming increasingly flourishing and promising, tourism organizations are also obliged to implement a series of organizational changes to adapt to the trending culturalization in the tourism domain. In light of this, this research, by outlining important sub-themes and trends of cultural tourism research, tracks the evolution of cultural tourism as a research field over the previous decades so as to analyze existing interconnections between the systematic review and tourism organizational change. Based on these interconnections, the research also manages to propose several potential implications for tourism organizations to optimize their future implement of daily organizational changes for the sake of adaptative survival and development.